Incorporation of impacted morselized bone allografts in rabbits - Judas, F (2005)
Morselized bone allografts have been used for the treatment of bone stock loss in orthopedic revision surgery with encouraging results. However, several parameters can influence the graft incorporation including the processing treatments. This experimental work used a cavitary bone defect in 90 rabbits to evaluate the sequence of incorporation of three different kinds of morselized bone allografts: uncryopreserved cancellous bone, freeze-dried cancellous bone, and totally demineralized cortical bone each of which were prepared in accordance with our rigid protocol. Revascularization and remodeling of the transplanted bone grafts were evident upon histological evaluation. Bone apposition and bone resorption resulted in a mixture of graft and new bone. Mineralized cancellous grafts showed great osteoconductive capacity, whereas demineralized cortical grafts showed an intense osteoinductive capacity and a weak osteoconductive capacity. In a general evaluation, cryopreserved cancellous bone grafts showed superior biological efficacy for reconstruction of experimental bone defects, closely followed by freeze-dried cancellous bone grafts, and, finally, by demineralized cortical bone grafts. These results validate our protocol for the processing and preservation of these three kinds of bone grafts.